Examining the application of nominalization in segmented abstracts: a corpus-based study - Yuan Yuwei (Journal of China Computer-Assisted Language Learning)
The aim of this study was to explore the use of nominalizations in segmented abstracts, examining their distribution and characteristics and whether they differ from traditional non-segmented abstracts in terms of the use of nominalizations. The study adopted a corpus-based approach, querying nominalization tokens using suffixes of nominalization, to analyse different sections of abstracts from 30 research articles in the American Journal of Psychiatry. Statistical analysis revealed that the Conclusions section among the four sections (Objective, Methods, Results, and Conclusions) utilized nominalizations most frequently, and a significant difference was found in the frequency of nominalizations between the four sections. The most frequently used suffixes of nominalization were -sion/-tion, followed by -ment and -ity, all of which reflected the functions of nominalization such as information condensation, cohesion construction, and agent or doer avoidance. Segmented abstracts show distinct strategies for the adoption of nominalizations in different sections. This study will contribute to English for Specific Purposes (ESP) in writing research articles.